Stakeholder Participation of Painted Terrapin Conservation in District Aceh Tamiang - Endang Hernawan; Sambas Basuni; Burhanuddin Masy'ud; Mirza Dikari Kusrini (Department of Forest Resources Conservation and Ecotourism - IPB University, 2018)
Painted Terrapin (Batagur borneoensis Schlegel and Muller 1845) conservation in the coastal area of Aceh Tamiang Regency faces difficulties because it involves many stakeholder. The objective of this study were to analyze stakeholder interest, influences and describe the relationship among stakeholder in the conservation of Batagur borneoensis at Aceh Tamiang District. The study was conducted in Aceh Tamiang District and respondents were selected using purposive sampling method. The data obtained using questionnaire, interview, and direct observation were analyzed with stakeholder clasification matrix, stakeholder interaction matrix and descriptive analysis. The results showed that there are twenty-seven stakeholder involved in the conservation of Batagur borneoensis which can be categorized as subjects, key players, context setters, and crowds. To achieve the management objectives of Batagur borneoensis conservation, stakeholder engagement needs to be improved through collaboration among key players, participation all key stakeholder, and community empowerment. Keywords: Batagur borneoensis, collaboration, conservation, stakeholder analysis